(untitled) - FAO (Rome, 1996)
It is complementary to the Programme for the World Census of Agriculture 2000 and provides much practical information on the steps involved in actually conducting an agricultural census either on a complete enumeration basis or a sample basis.
Keywords: agriculture - statistics